L'encadrement de mémoires et de thèses en sciences de l'éducation : enjeux et défis - France Jutras; Jean Gabin Ntebutse; Roland Louis
In the field of education, master and doctoral studies are considered too lengthy, and the dropout rate too high. One solution for improving the situation is to support supervision of studies. An explanatory study has been carried out at the Faculty of education at Université de Sherbrooke where material, financial, relational and intellectual conditions of supervision were examined. Data have been collected through semi-directive interviews and questionnaires distributed to research directors and students. The results highlight good practices and difficulties. The institution does provide support for the pursuit of studies and various aspects of scientific networking. However, individualized research training is achieved through the student's regular work supported by his director and, eventually, his participation in a research team. Finding a balance between their multiple tasks remains a considerable challenge for directors and students alike in the process leading up to the completion of the programme.